2021
DOI: 10.1007/s10877-021-00759-0
|View full text |Cite
|
Sign up to set email alerts
|

VACuum INtubation (VACcIN) box restricts the exhaled air dispersion generated by simulated cough: description and simulation-based tests of an innovative aerosolization protective prototype

Abstract: The COVID-19 pandemic has caused personal protective equipment shortages worldwide and required healthcare workers to develop novel ways of protecting themselves. Anesthesiologists in particular are exposed to increased risks of contamination when performing interventions such as airway manipulations. We developed and tested an aerosolization protective device which contains aerosols around the patient’s airway and helps eliminate particles using negative pressure. This intubation box is a polymethyl methacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…16 Previous studies on negative pressure aerosol boxes or vacuum-assisted aerosol boxes have proven their efficacy by showing reduced particles during intubation of a manikin. 19,20 Our previous study with Carrycure Isolator also proved its efficacy by showing a reduction of particles outside Carrycure Isolator during simulated AGMPs performed on a manikin. 12 To test Carrycure Isolator's efficiency, we measured the time to intubation along with the other secondary outcomes mentioned above.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…16 Previous studies on negative pressure aerosol boxes or vacuum-assisted aerosol boxes have proven their efficacy by showing reduced particles during intubation of a manikin. 19,20 Our previous study with Carrycure Isolator also proved its efficacy by showing a reduction of particles outside Carrycure Isolator during simulated AGMPs performed on a manikin. 12 To test Carrycure Isolator's efficiency, we measured the time to intubation along with the other secondary outcomes mentioned above.…”
Section: Discussionmentioning
confidence: 83%
“…Efficacy represents the ability to contain aerosol inside the box, usability refers to the user experience, and efficiency is indicated by the time to intubation [ 16 ]. Previous studies on negative pressure aerosol boxes or vacuum-assisted aerosol boxes have proven their efficacy by showing reduced particles during intubation of a manikin [ 19 , 20 ]. Our previous study with the Carrycure Isolator also proved its efficacy by showing a reduction of particles outside the Carrycure Isolator during simulated AGMPs performed on a manikin [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A plastic drape extending from the top of the box down to the patient’s chest prevents spread of aerosols . Suction tubing at the head of the aerosol box was added, as prior studies have demonstrated that continuous suction decreases airborne particle exposure . Wall suction was set at 200 mm Hg, measured to generate a negative airflow of approximately 50 L/min.…”
Section: Methodsmentioning
confidence: 99%
“… 15 , 17 , 28 Suction tubing at the head of the aerosol box was added, as prior studies have demonstrated that continuous suction decreases airborne particle exposure. 20 , 28 , 29 , 30 , 31 Wall suction was set at 200 mm Hg, measured to generate a negative airflow of approximately 50 L/min.…”
Section: Methodsmentioning
confidence: 99%